Edexcel GCSE (9-1) history : medicine in Britain c.1250-present & the British sector of the Western front, 1914-18. - Slater, Sam (Hodder Education Group, 2017)
Exam Board: EdexcelLevel: GCSESubject: HistoryFirst Teaching: September 2016First Exam: Summer 2018 Endorsed for EdexcelTarget success in Edexcel GCSE (9-1) History with this proven formula for effective, structured revision; key content coverage is combined with exam-style questions, revision tasks and practical tips to create a revision guide that students can rely on to review, strengthen and test their knowledge. With My Revision Notes, every student can: - Plan and manage a successful revision programme using the topic-by-topic planner - Enjoy an interactive approach to revision, wit.